Phylogenetic analysis of Black Bengal and Jamunapari goats in Bangladesh based on partial sequence of cytochrome b gene (SAARC Journal of Agriculture, 2019)
Goats, among the livestock species, are considered the most prolific ruminant especially under callous climatic conditions. The aim of the present study was to depict the current phylogenetic status and genetic diversities of Black Bengal (BBG) and Jamunapari goat of Bangladesh and the world. Cytochrome b (cytb) gene (1140 bp) of mitochondrial DNA of Black Bengal goats (Capra hircus) was amplified by Polymerase Chain Reaction (PCR) for the first time in Bangladesh. The sequence from BBG had no nucleotide (nt) difference and 100% homology with the BBG (C. hircus) of India and also the goats (C. hircus) from China (Yangtze River Delta White Goat), Thailand (Wild Cervidae), Japan (Bezoar goat) and South Africa (Domestic goat). The sequence had 1-5 nt differences and 99% homology with the goats (C. hircus) from China, Thailand and Japan (other goats), and also with the goats (C. hircus) from Malaysia, South Korea, France, Italy, Pakistan, Slovenia, Switzerland and USA. Phylogenetic tree constructed with Black Bengal Goat (BBG-K-2) and Jamunapari goats (SG-1) of Bangladesh with cytochrome b nucleotide sequences were closely related to China-HM7. China-YP xj46, Pakistan-Lineage C1, Pakistan-Lineage C2, Slovenia- ChSo1, Switzerland-ChTo2992 and shared 98.8% to 99% and 98.3% to 98.6% similarity, respectively and 1-1.2% and 1.4 to 1.7% genetic distance, respectively. Based on Ctb gene Sequence collected from Bangladeshi Black Bengal Goats (BBG-K-2) and Jamunapari goats (SG- 1) that were closely related and shared with the same genetic lineage of China HM18 and India-BBG-DQ073048, respectively, suggesting a common origin.SAARC J. Agri., 17(1): 23-35 (2019)